Beneficial Endophytic Bacteria-Serendipita indica Interaction for Crop Enhancement and Resistance to Phytopathogens - del Barrio-Duque, Alejandro; Ley, Johanna; Samad, Abdul; Antonielli, Livio; Sessitsch, Angela; Compant, Stéphane (Frontiers in Microbiology, 2019)
Serendipita (Piriformospora) indica is a fungal endophytic symbiont with the capabilities to enhance plant growth and confer resistance to different stresses. However, the application of this fungus in the field has led to inconsistent results, perhaps due to antagonism with other microbes. Here, we studied the impact of individual bacterial isolates from the endophytic bacterial community on the in vitro growth of S. indica. We further analyzed how combinations of bacteria and S. indica influence plant growth and protection against the phytopathogens Fusarium oxysporum and Rhizoctonia solani. Bacterial strains of the genera Bacillus, Enterobacter and Burkholderia negatively affected S. indica growth on plates, whereas Mycolicibacterium, Rhizobium, Paenibacillus strains and several other bacteria from different taxa stimulated fungal growth. To further explore the potential of bacteria positively interacting with S. indica, four of the most promising strains belonging to the genus Mycolicibacterium were selected for further experiments. Some dual inoculations of S. indica and Mycolicibacterium strains boosted the beneficial effects triggered by S. indica, further enhancing the growth of tomato plants, and alleviating the symptoms caused by the pathogens F. oxysporum and R. solani. However, some combinations of S. indica and bacteria were less effective than individual inoculations. By analyzing the genomes of the Mycolicibacterium strains, we revealed that these bacteria encode several genes predicted to be involved in the stimulation of S. indica growth, plant development and tolerance to abiotic and biotic stresses. Particularly, a high number of genes related to vitamin and nitrogen metabolism were detected. Taking into consideration multiple interactions on and inside plants, we showed in this study that some bacterial strains may induce beneficial effects on S. indica and could have an outstanding influence on the plant-fungus symbiosis.